2007
DOI: 10.1179/016164107x174138
|View full text |Cite
|
Sign up to set email alerts
|

Basic physiology of hyperbaric oxygen in brain

Abstract: Oxygen is the proverbial 'double-edged sword' in that it is a necessity for life in moderation and toxic and detrimental to life in excess. This too is the dilemma in hyperbaric oxygen (HBO) treatment in cerebral ischemic-anoxic insults such as stroke, head injury, near drowning, asphyxia, cardiac arrest, etc., i.e. the brain at risk, where regions of ischemia are beside regions of marked hyperemia. The natural heterogeneity of normal brain tissue oxygenation compounds the problem with different microvascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 39 publications
(48 reference statements)
0
34
0
Order By: Relevance
“…Animal experiments and clinical trials have shown that HBO performed within 6 h after HIBD may achieve favorable outcomes and promote the long-term neurological recovery (3)(4)(5)(6). In addition, numerous studies in China have demonstrated that HBO can reduce the disability and mortality of HIBD (7).…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments and clinical trials have shown that HBO performed within 6 h after HIBD may achieve favorable outcomes and promote the long-term neurological recovery (3)(4)(5)(6). In addition, numerous studies in China have demonstrated that HBO can reduce the disability and mortality of HIBD (7).…”
Section: Introductionmentioning
confidence: 99%
“…Food pellets and water were freely available throughout the experiment. Forty-eight rats were randomly divided into four groups: control group (rats with no injection), Sham group (physiological saline injected), model group (Aβ 25-35 injected) and HBO group (Aβ [25][26][27][28][29][30][31][32][33][34][35] injected+2ATA HBO treatment). Aβ [25][26][27][28][29][30][31][32][33][34][35] (SIGMA, USA, A4559) was dissolved at a concentration of 1g/L in sterile saline and incubated at 37°C for 7 days before use.…”
Section: Animals and Aß Preparationmentioning
confidence: 99%
“…The present study aimed to determine the effect of Hyperbaric oxygen (HBO) on Aß 25-35 induced cognitive deficits and oxidative stress and apoptosis effects in rats. Rats were given an injection of aggregated Aß [25][26][27][28][29][30][31][32][33][34][35] . After treatment with HBO for 20days, the learning and memory ability, hippocampus neuronal apoptosis, the activity of SOD, GSH content and the MDA level and mRNA and proteins expression of Bcl-2 and Bax were detected.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations